Greenland, southwest shore of Bontakoe Island, now Northeast Greenland National Park - Boyd, Louise Arner, 1887-1972 (1933)
Fig. 258 - Southwest shore of Bontekoe Island. Snow bank at foot of cliff with solifluction slope below it. July 16, 1933. (III). (Caption from Boyd, Louise A. (1935). The Fiord Region of East Greenland (pp. 173). New York: American Geographical Society.) Bontekoe Island, 1933 Boyd, Louise A. (1935). The Fiord Region of East Greenland. New York: American Geographical Society